Strategi Komunikasi Public Relations Pt. Koninis Fajar Mineral (KFM) dalam Meningkatkan Citra Perusahaan di Kabupaten Banggai Provinsi Sulawesi Tengah - Mursad, Ikswan; Kasma Amin; Andi Muttaqin (Journal of Media and Communication Studies, 2024)
The purpose of this research is to find out the public relations communication strategy of PT. Koninis Fajar Mineral in establishing cooperation between companies to improve the company's image at the nickel mining location in Banggai Regency, Central Sulawesi Province and to find out the form of cooperation between PT. Koninis Fajar Mineral between companies at the nickel mining location in Banggai Regency, Central Sulawesi Province. The type of research used is descriptive qualitative. Qualitative research is research or research that is descriptive (describes) and tends to use analysis. The result of this research is the Public Relations communication strategy of PT. Koninis Fajar Mineral (KFM) to improve the company's image at nickel mining locations in Banggai Regency, Central Sulawesi Province, is that the use of social media, company introduction, direct interaction with the community, and the role of the HSE Department are important strategies in maintaining the company's positive image. This combination of strategies shows serious efforts in improving communication, introducing the company effectively, understanding community needs, and ensuring a safe and healthy work environment. This emphasizes the importance of harmony, responsiveness and consistency in carrying out effective Public Relations practices and forms of cooperation. PT Koninis Fajar Mineral, in its operations at the nickel mine in Banggai Regency, Central Sulawesi, emphasizes cooperation between companies, evaluating KPIs related to sustainability, collaboration between management and leaders. companies, as well as engagement with government, the private sector and local communities through empowerment programs. This reflects their commitment to social responsibility, the environment and the welfare of the surrounding community.